Biological Soil Crusts in Agroecosystems - Kira Sorochkina; Clayton J. Nevins; Patrick W. Inglett; Sarah L. Strauss (EDIS)
Biological soil crusts, or biocrusts, are communities of microorganisms that form on the surface of soils, often found in deserts around the world. However, they can also occur in agroecosystems and potentially contribute nutrients to plants growing nearby. This publication is for those interested in learning more about what biocrusts look like and how they can impact agricultural soils.